Student’ Perspectives on Self-Assessment in English Language Teaching (ELT): The Implementation and Challenges at Tadulako University - Meilani, Melan; Usman, Sriati; Budi, Budi; Maf’ulah, Maf’ulah (Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigates students’ perspectives on self-assessment in English Language Teaching (ELT), focusing on its implementation and challenges at Tadulako University. The research employed a qualitative descriptive design supported by quantitative data to gain insights into students’ experiences. Data were collected through semi-structured interviews with five students and a five-point Likert-scale questionnaire administered to thirty students of the English Education Study Program who had experience using self-assessment in English courses. The data were analyzed using thematic analysis to identify key themes related to students’ understanding and challenges of self-assessment. The findings indicate that students perceive self-assessment as a reflective learning process that helps them monitor progress, identify strengths and weaknesses, and take responsibility for learning. Self-assessment enhanced motivation, confidence, learner autonomy, and English language skills. However, challenges such as limited objectivity, unclear assessment criteria, and insufficient lecturer feedback were identified. These findings suggest self-assessment requires guidelines, rubrics, and lecturer support.